The relationship between ProNT BNP levels and erectile dysfunction in patients with chronic congestive heart failure (Annals of Medical Research, 2021)
Aim: Dysfunction and impairment of many organs occur in chronic congestive heart failure due to ischemia and stasis. Chronic congestive heart failure is frequently accompanied by erectile dysfunction since the two conditions have many etiologic factors in common. Our aim in the study was to investigate the potential relationship between ProNT BNP levels, which show the severity of cardiac failure, and erectile dysfunction in patients with an ejection fraction of 30-40%. Materials and Methods: The study included 72 male patients followed-up for chronic congestive heart failure. for whom erectile dysfunction was investigated. International Erectile Function Index-5 (IIEF-5) questionnaire was questioned to the patients to evaluate erectile function.Results: The mean age, total testosterone and lipids (low and high-density lipoprotein cholesterol triglyceride) levels did not significantly differ between the groups (P > 0.05). The mean ProNT BNP levels belonging to all subgroups showed statistically significant differences and correlated with the severity of erectile dysfunction according to the Kruskal-Wallis test (p0.001).Conclusions: In patients with chronic congestive heart failure, ProNT BNP was higher, and the severity of erectile disfunction was similarly increased.
Keywords: Chronic congestive heart failure; erectile dysfunction; ProNT BNP